Role of Agni in Panchakarma Practice: A Conceptual Study (International Journal of Ayurveda and Pharma Research, 2023)
Panchakarma is a complex system of the expulsion of vitiated Doshas i.e., toxins, or waste and thus inducing purification of the body. They are therapeutic emesis (Vamana), therapeutic purgation (Virechana), decoction enema (Niruha Vasti), oil enema (Anuvasana Vasti), and instillation of medicine through the nose, (Nasya). All Panchakarma procedures are carried out in three stages known as Poorvakarma (pre-operative procedures), Pradhanakarma (operative procedures), and Paschat karma (post-operative procedures). Agni has a very important role in all these Poorva-Pradhana and Paschat karma. The order of Panchakarma starts with Deepana-Pachana. Then Sneha-Sweda and Pradhana karma. The role of Deepana-Pachana is the correction of deranged Agni. Because a Dravya has to get digested properly by the Jatharagni after which it starts its action, Exception for this in Vamana dravya. Furthermore, following Pradhana karma, the body experiences Suddhi as a result of the removal of Doshas, which results in Agnimandya. Agnimandya is corrected by Samsarjana krama. Thus, the successful administration of Panchakarma is solely dependent on the person's Agni status. So, in this paper, a humble attempt is made to understand the role of Agni in Panchakarma practice.